Human Factors and Health-Care Professionals Collaboration to Reduce Alarm Fatigue in ICU Settings at a Large Academic Medical Center. Issue 1 (June 2016) - Mayer, Celeste; Mauney, Jennifer; Barnes, Janey; Addison, Ashley; Dicus, Andrea K.; Hanlin, Ryan; Hsieh, Kelsy B.; Soares, Sharmila; White, Brittany L.
Key stakeholders across healthcare's complex socio-technical environment have been called by the Joint Commission to take part in the shared responsibility to improve alarm safety. This project demonstrated the value added from applying Human Factors principles to a process supporting the safety of patients and the work of health-care providers by reducing the non-actionable alarms in 4 in-patient care units. An Alarm Safety Quality Improvement project is described with specific objectives, methods and results. Results from this project demonstrated an iterative process which provided data and empowerment to the team. The data provided the unit leaders new actionable information and targeted intervention planning with associated meaningful measurements. The process has empowered units to tackle alarm fatigue with the necessary knowledge, tools, and support. The four in-patient care units that have completed this process saw a combined average weekly decrease of 14, 000 alarms.